Quartzite an Ganister-Raw Materials for Refractories from N.W.F.P. and Punjab - Ashraf, Muhammad; Qureshi, M. Hanif; Faruqi, F.A. (Journal of Himalayan Earth Sciences, 1975)
Quartzite and ganister have been located and studied from different areas of NWFP and Punjab for the manufacture of silica refractories. Brief geology of silica bearing rock of those areas is given and discussed. In the laboratory the samples were studied and analysed for their mineral constituents and oxide components. Furthermore; their physical properties have been evaluated for suitable uses for the manufacture of Silica refractories. It is found out that quartzite from Attock and Haripur area is one of hte best for refractory purposes while ganister from Musakhel and quartzite from Swabi and Terbela can be used for making semi-silica bricks.